2018
DOI: 10.1007/s40820-018-0221-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Synthesis and Properties of Hybrid Halide Perovskites for Photovoltaics

Abstract: The progress made by the scientific community in emerging photovoltaic technologies over the past two decades has been outstanding. Numerous methods have been developed for the preparation of hybrid organic–inorganic perovskite solar cells. The power conversion efficiency has been up to 14% by a one-step vacuum deposition technique. A serious concern is the toxicity of the materials. In this review, several methods aimed at resolving these problems to some extent have been compiled, including eco-friendly synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 240 publications
(217 reference statements)
0
54
0
Order By: Relevance
“…As in the case of graphite and carbon black back electrodes, organic [227][228][229] and inorganic 149 HTMs have been exploited to further increase the hole extraction ability of CNTs. 230,231 Aitola et al reported a CNT-based PSC with spiro-OMeTAD as the HTM. 228 An average PCE of 14.3% was achieved, still lower than that obtained with gold as the back electrode (18.4%).…”
Section: Carbon Nanotube-based Back Electrodesmentioning
confidence: 99%
“…As in the case of graphite and carbon black back electrodes, organic [227][228][229] and inorganic 149 HTMs have been exploited to further increase the hole extraction ability of CNTs. 230,231 Aitola et al reported a CNT-based PSC with spiro-OMeTAD as the HTM. 228 An average PCE of 14.3% was achieved, still lower than that obtained with gold as the back electrode (18.4%).…”
Section: Carbon Nanotube-based Back Electrodesmentioning
confidence: 99%
“…PVD and CVD seem more suited for the deposition of uniform films on textured substrates. Nevertheless, a variety of charge transport and charge blocking layers has been suggested and successfully implemented including well-established materials like Spiro-MeOTAD and TiO 2 or novel materials like graphene oxide or Cu-phthalocyanine [78][79][80][81][82][83]. Furthermore, it might be necessary to use multiple layers to fulfill all the requirements of the contact layers.…”
Section: Device Design and Materials Propertiesmentioning
confidence: 99%
“…There are many factors at the preparation stage which can induce defects in MHP . However, when the sample is already prepared, ion migration is probably one of the most important phenomenon responsible for further sample evolution and its eventual degradation .…”
Section: Possible Mechanisms Of Pl Response Of Mapbx3 Polycrystals Tomentioning
confidence: 99%
“…[27] There are many factors at the preparation stage which can induce defects in MHP. [40,41] However, when the sample is already prepared, ion migration is probably one of the most important phenomenon responsible for further sample evolution and its eventual degradation. [17,18,42] The dominant species for ion migration are most likely the halogen ions (e.g., I − in MAPbI 3 ), however MA + and others can also migrate but with higher activation energy.…”
Section: Possible Mechanisms Of Pl Response Of Mapbx 3 Polycrystals Tmentioning
confidence: 99%